Anticholinergic drugs and physical function among frail elderly population - Landi, F; Russo, A; Liperoti, R; Cesari, M; Barillaro, C; Pahor, M; Bernabei, R; Onder, G (Clinical pharmacology and therapeutics, 2007)
Increasing evidence from experimental studies and human observations suggests that drugs with anticholinergic properties can cause physical and mental impairment. The aim of this study was to evaluate the relationship between the use of drugs with anticholinergic activity and measures of physical performance, muscle strength, and functional status in persons aged 80 years or older. Data are from baseline evaluation of 364 subjects enrolled in the ilSIRENTE study. The ilSIRENTE study is a prospective cohort study performed in the mountain community living in the Sirente geographic area (L'Aquila, Abruzzo) in Central Italy. Physical performance was assessed using the physical performance battery score (Short Physical Performance Battery), which is based on three timed tests: 4-meter walking speed, balance, and chair stand tests. Muscle strength was measured by hand grip strength. We defined as anticholinergic drugs all medications for which serum anticholinergic activity was previously demonstrated. Analyses of covariance were performed to evaluate the relationship of anticholinergic drugs with physical function. In the unadjusted model, all the physical performance, muscle strength, and functional measures showed significant associations with the anticholinergic drug use. After adjustment for potential confounders (age, gender, smoking, physical activity level, cognitive performance score, living alone, body mass index, congestive heart failure, lung diseases, diabetes), these associations were weaker but still statistically significant (physical performance battery score: non-users anticholinergic drugs 6.9, SE 0.1, users anticholinergic drugs 6.1, SE 0.2, P=0.05; hand grip strength: non-users anticholinergic drugs 31.3 kg, SE 0.8, users anticholinergic drugs 28.8 kg, SE 1.0, P=0.05; Activities of Daily Living scale score: non-users anticholinergic drugs 1.2, SE 0.1, users anticholinergic drugs 1.6, SE 0.1, P=0.03; Instrumental Activities of Daily Living scale score: non-users anticholinergic drugs 2.7, SE 0.1, users anticholinergic drugs 3.4, SE 0.1, P<0.001). The use of medication with anticholinergic properties is common among community older subjects in Italy. Our results suggest that among old-old subjects the use of anticholinergic drugs is associated with impaired physical performance and functional status.